BUSINESS DEVELOPMENT STRATEGY WITH CANVAS MODEL BUSINESS APPROACH IN CV. HAKHENBIK - Kamaluddin, Iqbal (Dinasti International Journal of Economics, Finance & Accounting, 2020)
Hakhenbik is a company engaged in the field of furniture and equipment of the school with its production material made from solid wood that has durable strength, and not easily damaged and has a high selling price. On this research author uses qualitative descriptive method that is by using the business model Business model Canvas (BMC), then evaluated using a SWOT analysis in every Business model Canvas (BMC) block on CV. Hakhenbik. The most powerful element in the Business Model Canvas is the Key Partnership, sis the value propositions. The elements that still lack are Customer Relationships and the next is Key Resources. Be rbased on SWOT analysis, CV. Hakhenbik is advised to improve on the element of customer relationshipsThis is because the important factor in running the business is to maintain good relations with the customer, one way to maintain a good relationship with the customer is to maintain communication with customers such as increase communication through social media such as facebook, whats up group, Instagram and others, and can be done by maintaining loyal customers by providing members cards and discounts for loyal customers. In addition to the customer relationships elements that need to be repaired are key Resources by conducting training and development to employees of both operational and management employees.